Empowering newcomers? Power asymmetries and negotiations between newly arrived migrants and volunteers within buddy programmes - Gaëlle Mortier; Stijn Oosterlynck; Peter Raeymaeckers (International Journal of Evidence Based Coaching and Mentoring)
Research on buddy programmes for newly arrived migrants focuses predominantly on integration outcomes. However, the intervention is also prone to reproducing power imbalances. This qualitative study investigates how power asymmetries between volunteers (buddies) and immigrant newcomers are characterized. We draw on interview data to scrutinize how power is reproduced and negotiated in the dyadic relationships within buddy programmes. Both practices of Othering and De-othering take place, resulting in mixed networking outcomes for newcomers in the host society. The findings provide important insights for policy and practice, employing buddy programmes as a tool for fostering migrant integration.